Macroanatomical and subgross studies on the brachial plexus of the akkaraman sheep - Memduh Gezici (Eurasian Journal of Veterinary Sciences)
In this study, the formation and distribution of the brachial plexus were investigated in Akkaraman sheep, for this purpose, eight Akkaraman sheep in different ages and sex were used. It was observed that the brachial plexus in the Akkaraman sheep was formed by the ventral branches of the sixth, seventh, eight cervical and first thoracic spinal nerves. It was seen that there wasn't a significant difference in the courses and distributions of the nerves arising Irom the brachial plexus in Akkaraman sheep and other sheep.